A Case of False Negative NIPT for Down Syndrome-Lessons Learned - Meagan Smith; Kimberly M. Lewis; Alexandrea Holmes; Jeannie Visootsak (Case Reports in Genetics)
Down syndrome or trisomy 21 is the most common cause of prenatal chromosome abnormalities with approximately 50% of all reported chromosome conditions. With the successful introduction of noninvasive prenatal testing (NIPT) for Down syndrome into routine prenatal care, it is important to understand the risks, benefits, and limitations in order to guide patients in making an informed decision. Herein, we describe the first published case report of a patient whose fetus tested “negative” for Trisomy 21 by NIPT but was diagnosed postnatally with trisomy 21. We present the importance of proper pretest and posttest genetic counseling to ensure prenatal patients are able to make informed decisions and are educated appropriately about NIPT.